The Grain Market in India and the Creation of the BRICS Grain Union - A. Ivanov; K. Molodyko; M. Kalimullina (BRICS Law Journal, 2022)
The article examines the current situation in the wheat market in India and its potential within the global food security dynamic. In particular, it analyzes a number of instruments and programs of national policy in the grain sector: minimum support prices, public procurement, public distribution systems, storage facilities and their management, market regulation, trading mechanisms and platforms. In the aspect of the development of Indian grain trade and infrastructure, the Electronic Platform for National Agriculture Market (eNAM) and food commodities exchanges are considered. The article provides explanation on why India’s ambitious plans announced several years ago to expand wheat exports to the world market can hardly be fully realized in the near future due to such reasons as climate risks, phytosanitary problems and quality controls, lack of storage and logistics infrastructure, as well as the huge social and political importance of wheat supplies in the local market. Through the continuation of the current reforms in an efficient manner, India can resume the position of one of the leading wheat exporters. It is proposed that Russia, India and South Africa (as well as the potential new members – Iran and Argentina) create anew BRICS Grain Union.